375. High Laboratory-confirmed SARS-CoV-2 Attack Rate in Lima Health Care Personnel During August 2020-March 2021 Suggests Role for Improved Infection Control. (4th December 2021) - Westercamp, Matthew; Soto, Giselle; Smith, Rachel; Azziz-Baumgartner, Eduardo; Bollinger, Susan; Castillo, Roger; Cuentas, Alejandro Llanos; Grogl, Max; Olson, Natalie; Prouty, Mike; Matos, Eduardo; Romero, Candice; et al.
Abstract: Background: Peru has one of the highest per capita SARS-CoV-2 death rates in Latin America. Healthcare workers (HCW) are a critical workforce during the COVID-19 pandemic but are themselves often at increased risk of infection. We evaluated SARS-CoV-2 attack rate and risk factors among frontline HCWs. Methods: We performed a prospective cohort study of HCW serving two acute care hospitals in Lima, Peru from Aug 2020 to Mar 2021. Participants had baseline SARS-CoV-2 serology using the CDC ELISA, active symptom monitoring, and weekly respiratory specimen collection with COVID-19 exposure/risk assessment for 16-weeks regardless of symptoms. Respiratory specimens were tested by real-time reverse transcriptase PCR (rRT-PCR). Results: Of 783 eligible, 667 (85%) HCW were enrolled (33% nurse assistants, 29% non-clinical staff, 26% nurses, 7% physicians, and 6% other). At baseline and prior to COVID-19 vaccine introduction, 214 (32.1%; 214/667) were reactive for SARS-CoV-2 antibodies. In total, 72 (10.8%; 72/667) HCWs were found to be rRT-PCR positive during weekly follow-up. Of the rRT-PCR positive HCWs, 37.5% (27/72) did not report symptoms within 1-week of specimen collection. During follow up, HCW without detectable SARS-CoV-2 antibodies at baseline were significantly more likely to be rRT-PCR positive (65/453, 14.3%) compared to those with SARS-CoV-2 antibodies at baseline (4/214, 1.9%) (p-value: < 0.001). Three HCW were both serologically reactive and rRT-PCR positive at baseline. Looking only at HCW without SARS-CoV-2 antibodies, nurse assistants (rRT-PCR positive: 18.6%; 27/141) and non-clinical healthcare workers (16.5%; 21/127) were at greater risk of infection compared to nurses (8.5%; 10/118), physicians (7.9%; 3/38), and other staff (10.3%; 4/29) (RR 1.95;95%CI 1.2, 3.3; p-value: 0.01). Conclusion: Baseline SARS-CoV-2 prevalence and 16-week cumulative incidence were substantial in this pre-vaccination Peruvian HCW cohort. Almost 40% of new infections occurred in HCW without complaint of symptoms illustrating a limitation of symptom-based HCW screening for COVID-19 prevention. Nurse assistants and non-clinical healthcare workers were at greater risk of infection indicating a role for focused infection prevention and risk reduction strategies for some groups of HCW. Disclosures: Fernanda C. Lessa, MD, MPH, Nothing to disclose